The impact of perioperative positive fluid balance on postoperative acute kidney injury in patients undergoing open hepatectomy: A retrospective single center cohort study - Natsuda Phothikun; Orapan Pantatong; Maytinee Kulpanun; Somchai Wongpunkamol; Worakitti Lapisatepun; Amarit Phothikun; Warangkana Lapisatepun (PLoS ONE, 2025)
Background Low central venous pressure (CVP) or fluid restriction strategies are frequently employed during liver parenchymal resection to minimize intraoperative blood loss. However, both hypovolemia and excessive fluid administration can impair organ perfusion, increasing the risk of renal dysfunction and acute kidney injury (AKI). This study explores the relationship between perioperative fluid management strategies and renal outcomes in patients undergoing hepatectomy. Method A retrospective single-center cohort study was conducted involving 691 patients who underwent an open hepatectomy. Patients were categorized by positive fluid balance: <1 Liter, 1-2 Liters, and >2 Liters. Propensity score was used for matching among the groups. The incidence of acute kidney injury (AKI) was compared. Multivariable logistic regression analyzed the correlation between fluid balance and AKI risk. Result The overall incidence of AKI was 11.58%, with the highest occurrence in the group with a fluid balance greater than 2 Liters. This group demonstrated a significantly higher relative risk of developing AKI compared to those with positive fluid balances of <1 Liter and 1-2 Liters (adjusted RR 1.85, p = 0.042, 95% CI 1.02-3.38). An increase in fluid balance was associated with a higher incidence rate ratio for AKI (p = 0.016). Additionally, an operating time >5 hours, blood loss >1000 ml, and Child-Turcotte-Pugh class B and C were significantly associated with an increased risk of post-hepatectomy AKI. Conclusion Maintaining a fluid balance of 1-2 liters during hepatectomy is crucial to reducing the risk of postoperative AKI, while balances above 2 liters significantly increase it. Prolonged operating times, high blood loss, and advanced liver disease also elevate AKI risk, emphasizing the need for careful fluid management.